Lithium Loaded Octa‐Poly(Ethylene Glycol) Based Adhesive Facilitates Axon Regeneration and Reconnection of Transected Peripheral Nerves. Issue 13 (19th May 2020) - Bu, Yazhong; Wang, Xianghai; Li, Lixia; Hu, Xiaofang; Tan, Dandan; Li, Zhenlin; Lai, Muhua; Qiu, Xiaozhong; Sun, Feifei; Wang, Hufei; Yang, Fei; Wu, Decheng; et al.
Abstract: At present, reconnecting the transected nerve in clinic is still mainly reliant on surgery suture. This is a procedure that requires thorough training and is also time consuming. Here, an octa‐poly(ethylene glycol) (PEG)‐based adhesive for fast reconnecting of the transected peripheral nerve is reported. To enhance the therapeutic efficacy, a succinyl unit is applied to endow the controllably dissolvable property of the adhesive, and lithium is loaded in the adhesive to improve the axonal regeneration. Present data reveal that this adhesive possesses good cytocompatibility and can significantly shorten the reconnecting time of the transected nerve ends compared to that required for suture surgery. Histology, electrophysiological, and behavior assessments indicate that the adhesive reconnected nerves exhibit a low grade of fibrosis, inflammation response, and myoatrophy as well as robust axonal regeneration and functional recovery. Together, these results indicate that this octa‐PEG adhesive can act as an alternative to traditional nerve suture in peripheral nerve injury. Abstract : A LiCl‐loaded PEG adhesive with controllably dissolvable properties is constructed for reconnecting the transected peripheral nerve and facilitates the axonal regeneration, of which the theraputic effect is nearly the same as that of a suture.